Assessing the Quality and Reliability of COVID-19 Information on Patient Organization Websites - Brown, Erin E. (Frontiers in Communication, 2021)
This article used a content analysis method utilizing the Centers for Disease Control and Prevention’s Clear Communication Index to evaluate the quality and reliability of 15 patient organization websites that are designed for patients to have access to information about COVID-19. The objective of this content analysis was to assess the clarity of online communication of information on COVID-19 by patient organizations by determining how well the websites score for clarity and identify ways to improve the websites. This study suggests that the patient organization websites that were analyzed are not adequately designed to communicate relevant information about COVID-19 in meaningful and effective ways. The findings from this study will help reveal major deficits in the communication of COVID-19 health information on patient organization websites, identify best practices and improvements that can be made to enhance communication, and build on existing literature regarding e-health literacy and clear communication on public health websites.